Legal Values for Improved Good Governance through National Legal Reform - Habibi, Dani; Utama, Yos Johan; Putrijanti, Aju (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 2 (2024)DO - 10.24843/JMHU.2024.v13.i02.p10., 2024)
The fundamental principles of effective governance serve as the primary foundation guiding governmental actions aimed at addressing societal needs. These actions are delineated in Law Number 30 of 2014 concerning Government Administration. This article delves into the imperative of crafting legal tenets that are attuned to the overarching principles of good governance, thereby advancing national legal reforms in pursuit of effective governance. Employing a normative legal research methodology encompassing statutory regulation and conceptual analyses, this study underscores the necessity of integrating responsive legal values into Law Number 30 of 2014 to comprehensively address the diverse needs of the populace in government services. Furthermore, augmenting the general principles of good governance with responsive legal values underscores the national commitment to legal revitalization, necessitating governmental enhancements in fulfilling community needs through service provision. Keywords: General Principles of Good Government, Responsive Law, Government, Good Governance.